RyR1-mediated Ca 2+ -induced Ca 2+ release plays a negligible role in excitation–contraction coupling of normal skeletal muscle - Takuya Kobayashi; Toshiko Yamazawa; Nagomi Kurebayashi; Masato Konishi; Jun Tanihata; Masami Sugihara; Yoshifumi Miki; Satoru Noguchi; Yukiko U. Inoue; Takayoshi Inoue; Takashi Sakurai; Takashi Murayama (Proceedings of the National Academy of Sciences, 2025)
Type 1 ryanodine receptor (RyR1) is a Ca 2+ release channel in the sarcoplasmic reticulum in skeletal muscle. In excitation–contraction (E-C) coupling, RyR1 opens by depolarization of transverse tubule membrane via physical interaction with dihydropyridine receptor, which is referred to as depolarization-induced Ca 2+ release (DICR). RyR1 can also be gated via Ca 2+ -induced Ca 2+ release (CICR), in which binding of Ca 2+ directly opens the channel. Thus, RyR1 has two Ca 2+ release modes; DICR and CICR, but the physiological role of CICR has been a matter of debate: whether CICR can amplify Ca 2+ signals in E-C coupling. To address this issue, we created a mouse model carrying a mutation in the Ca 2+ -binding site in RyR1 (RyR1-E3896A), which selectively inhibits CICR. Surprisingly, the homozygous RyR1-E3896A mice show no appreciable changes in E-C coupling, ex vivo muscle contraction, in vivo muscle performance, or muscle fiber type. Gain-of-function mutations in RyR1 cause malignant hyperthermia (MH), which is a lethal disease triggered by inhalational anesthetics. The E3896A mutation conferred resistance to isoflurane-induced MH episodes and severe heat stroke triggered by environmental heat stress. Our data suggest that RyR1-mediated CICR plays a negligible role in E-C coupling of normal skeletal muscle but may increase the risk for muscle diseases when excessively activated.